RANCANGAN TEKNIS SISTEM PENYALIRAN PADA KOLAM PENGENDAPAN (SETTLING POND) DI PIT DURIAN PT. J RESOURCES BOLAANG MONGONDOW SITE BAKAN, SULAWESI UTARA - Surahmad, Regita Cahyani (ReTII, 2021)
ABSTRACT PT. J Resources Bolaang Mongondow (PT. JRBM) is one of the gold mining companies that implements an open pit mining system (surface mining) with the open pit method. The mining operation area is located at the Bakan Site, namely in Bakan Village, Lolayan District, Bolaang Mongondow Regency, North Sulawesi Province. The series of mining operations starts from overburden stripping, drilling, blasting, loading, and transporting. With the mining activities carried out by PT. J Resources Bolaang Mongondow (PT. JRBM) will have an impact on environmental quality, especially on water quality. Due to the wide range of problems and benefits of water, water management is important in the mining industry. So that a mine drainage system method is used for handling water that will pollute rivers, lakes, and the surrounding environment by making a settling pond. Settling pond function to deposit mud or other materials so that the water flowing from the settling ponds to the river is clear, besides that this is also intended to prevent silting of the river. Settling pond can also function as a place to control the quality of the water that will flow out of the settling pond. The design of the settling pond that will be made is based on the total flow of water entering the settling pond, which is 3,784 m3/second with each amount of incoming water consisting of a runoff water discharge of 3,78 m3/second and the rainwater discharge is 0,0048 m3/second. Settling pond are designed to be in the shape of a truncated pyramid and made zigzag. The designed settling pond consists of 5 compartments with dimensions of 6.045 m2, depth 7 m, pool slope 60Ëš, top width 21 m, top length 39 m, bottom width 13 m, bottom length 30 m, and the total volume of the pond. the design is 20.700 m3 with the volume of each compartment of 4.140 m3. As well as the sedimentation pond that is designed also consists of 4 pieces of insulation with a width of 7 m and a length of 14 m. From the dimensions of the designed settling pond of 20.700 m3, it can accommodate the incoming water volume of 20.331 m3 for 89,55 minutes. The settling pond must be maintained so that it can function properly and for a long time, namely by cleaning the settling pond from solid material that settles to the bottom of the pond using a 390D L paint excavator. For each compartment of the settling pond has a different maintenance time in each compartment. i.e. in compartment 1 maintenance can be carried out once every 7 days, compartment 2 is carried out once every 68 days, compartment 3 is carried out once every 586 days, compartment 4 is carried out once every 4.140 days or Â±11 years, and compartment 5 is carried out once every 37.636 days or Â±103 years, but in compartment 5 there is no need for maintenance because it has passed the mine life limit at the company. Keywords : Pond, Sediment, Discharge, Dimensions, Maintenance.